Implementasi Pemenuhan Hak Pendidikan Anak Usia Dini Sanggar Belajar Segambut Malaysia - Alisa, Salsabila Rizqi Ramadhanty; Pranoto, Yuli Kurniawati Sugiyo (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
This research is motivated by the importance of fulfilling the right to early childhood education for migrant children in Malaysia who still face various challenges. This study aims to analyze the fulfillment of early childhood education rights in Segambut Learning Studio Malaysia, with a focus on learning strategies, curriculum implementation, facilities, implementation constraints, and the impact of implementation on early childhood. A qualitative approach was used with a phenomenological method, through participant observation, in-depth interviews with one educator and three parents, and photo documentation of learning activities. Data analysis was conducted using an interactive model: data collection, data reduction, and conclusion drawing. Results show that the curriculum is tailored to children's needs through faith-based learning, culture, and social and emotional support. However, limited facilities, resources and children's motivation to learn are a challenge, as are policies, funds and the environment. This research contributes to recommending policy integration between Indonesia and Malaysia and strengthening community support. Collaborative efforts between government, communities and institutions are needed to realize an inclusive education environment for all migrant early childhood in Malaysia without exception.